THE EFFECT OF VITAMIN E AND DEXAMETASONE ON THE WHITE RATS BRAIN - Umam, Afrizal Choirul; Berata, I Ketut; Samsuri, Samsuri; Sudira, I Wayan; Sudimartini, Luh Made; Merdana, I Made (Buletin Veteriner Udayana, 2018)
Provision of dexamethasone for the long term and large doses may cause disturbances in the brain. To prevent disruption to the brain, it needs antioxidant such as vitamin E. The aims of this study is to prove the administration of dexamethasone cause interference on white rat brain and determine the effects of vitamin E supplementation in preventing the side effects of dexamethasone in the brains of rats. This study used 25 male rats were divided into 5 groups, namely negative control was only given food and drink, positive control is given dexamethasone at a dose of 0.13 mg/kg bw, P1 given dexamethasone 0.13 mg/kg of body weight and vitamin E at a dose of 100 mg/kg bw, P2 given dexamethasone 0.13 mg/kg bw and vitamin E at a dose of 150 mg/kg bw, P3 given dexamethasone 0.13 mg/kg bw and vitamin E at a dose of 200 mg/kgbw. Treatment was given for 14 days, then the experimental animals necropsied. Brain tissue was taken and processed for making histopathology preparations using hematoxylin-eosin staining. Variables examined include perivascular edema lesions and congestion. The result found a significant difference between negative and positive control. The mean score improvement of brain damage was not significantly different between the treatment P1, P2, and P3. P1 treatment groups showed mean score approached the negative control. The conclusions of this research was the dexamethasone caused histopathological changes to rat brains. Supplementation of vitamin E up to doses of 200 mg /kg of body weight have not been able to reduce the side effects of dexamethasone on the brain.